Uncertain Times : Kenneth Arrow and the Changing Economics of Health Care - Hammer, Peter Joseph (Book collections on Project MUSE., 2003)
This volume revisits the Nobel Prize-winning economist Kenneth Arrow & rsquo;s classic 1963 essay & ldquo;Uncertainty and the Welfare Economics of Medical Care & rdquo; in light of the many changes in American health care since its publication. Arrow & rsquo;s groundbreaking piece, reprinted in full here, argued that while medicine was subject to the same models of competition and profit maximization as other industries, concepts of trust and morals also played key roles in understanding medicine as an economic institution and in balancing the asymmetrical relationship between medical providers and their patients. His conclusions about the medical profession & rsquo;s failures to & ldquo;insure against uncertainties & rdquo; helped initiate the reevaluation of insurance as a public and private good. Coming from diverse backgrounds & mdash;economics, law, political science, and the health care industry itself & mdash;the contributors use Arrow & rsquo;s article to address a range of present-day health-policy questions. They examine everything from health insurance and technological innovation to the roles of charity, nonprofit institutions, and self-regulation in addressing medical needs. The collection concludes with a new essay by Arrow, in which he reflects on the health care markets of the new millennium. At a time when medical costs continue to rise, the ranks of the uninsured grow, and uncertainty reigns even among those with health insurance, this volume looks back at a seminal work of scholarship to provide critical guidance for the years ahead. Contributors Linda H. Aiken Kenneth J. Arrow Gloria J. Bazzoli M. Gregg Bloche Lawrence Casalino Michael Chernew Richard A. Cooper Victor R. Fuchs Annetine C. Gelijns Sherry A. Glied Deborah Haas-Wilson Mark A. Hall Peter J. Hammer Clark C. Havighurst Peter D. Jacobson Richard Kronick Michael L. Millenson Jack Needleman Richard R. Nelson Mark V. Pauly Mark A. Peterson Uwe E. Reinhardt James C. Robinson William M. Sage J.B. Silvers Frank A. Sloan Joshua Graff Zivin.